RESEARCH TRENDS IN ISLAMIC FAMILY LAW: A BIBLIOMETRIC ANALYSIS OF SCOPUS PUBLICATIONS (2000–2024) - Galuh Widitya Qomaro; Mohammad Hipni; Zakiyatus Soimah; Erie Hariyanto; Nurfadhilah Che Amani (Jurnal Al-Dustur, 2026)
The last 20 years have seen a growing interest in Islamic Family Law among scholars with a significant number of studies being published in international settings. The current paper evaluates the trend in the research activities in relation to Islamic Family Law across the world between the year 2000 and the year 2024. This study used data out of the Scopus journal. A systematic bibliometric analysis shows that the number of articles has grown since 2015 because of the increased interest in women's issues worldwide, the necessity to introduce changes in Muslim states, and the connection between the Islamic family law and other legal systems. Malaysia, Indonesia, Pakistan and Egypt are also considered to be some of the pioneer countries which study Islamic Family Law and the western countries that have a problem of Muslim minority also have made remarkable contributions in the study of Islamic Family Law. This paper is a critique and synthesis of the literature on issues like polygamy, divorce, and child marriage through sentiment analysis and elicits the potential opinions at both ends of the spectrum. The results indicate that research on Islamic Family Law has expanded across multiple dimensions. However, the NVivo thematic coding reveals recurring concerns regarding compatibility between Islamic family law and international human rights norms, particularly in discussions on gender equality and child marriage. This paper intends to scope the existing field in hopes of covering contemporary discourses by focusing on the Islamic Family Law research field and detailing the evolution of the field and mapping its prominent scholars.